Childhood trauma, dissociation, and the internal eating disorder 'voice'. (December 2018) - Pugh, Matthew; Waller, Glenn; Esposito, Mirko
Abstract: Many individuals diagnosed with eating disorders describe their disorder as being represented by an internal 'voice'. In line with cognitive models of voice-hearing, previous research has identified associations between voice appraisals and eating psychopathology in anorexia nervosa. Whether these findings generalise to other eating disorder subtypes remains unknown. The aetiology of the internal eating disorder voice also remains unclear. Traumatic-dissociative models of voice-hearing, which link such experiences to decontexualised material arising from early traumatic events, might also be relevant to eating disorder groups. To determine whether cognitive models of trauma and voice-hearing apply across eating disorder subtypes, 85 individuals fulfilling ICD-10 criteria for an eating disorder completed self-report measures regarding eating disorder cognitions, voice-related appraisals, childhood trauma, and dissociation. The relative power of the eating disorder voice was found to be positively associated with experiences of childhood emotional abuse, and this relationship was partly mediated by dissociation. In addition, eating disorder voices appraised as powerful and benevolent predicted more negative attitudes towards eating across diagnostic groups, but were unrelated to disordered eating behaviours or weight. These findings suggest that the eating disorder voice plays a meaningful role in eating pathology across diagnoses and that this experience might be related, in part, to experiences of childhood maltreatment. Therapeutic implications are discussed.